2018
DOI: 10.1590/0102-311x00202816
|View full text |Cite
|
Sign up to set email alerts
|

Introdução de alimentos não recomendados no primeiro ano de vida e fatores associados em crianças de baixo nível socioeconômico

Abstract: The study aimed to identify factors associated with the introduction of inappropriate complementary feeding in the first year of life in children living in municipalities (counties) with low socioeconomic statusl. This was a cross-sectional multicenter study in 1,567 children 12 to 59 months of age in 48 municipalities participating in the Brazil Without Poverty plan in the South of Brazil. A structured questionnaire was applied to the children's parents to obtain socio-demographic information and the age at w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
37

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 36 publications
1
24
0
37
Order By: Relevance
“…In addition, we observed an elevated prevalence of UPF consumption for all The total was lower for some variables due to missing information children. These results are similar to other studies that evaluated early childhood food consumption in Brazil [10,25]. UPF consumption in the first 2 years of life is not recommended because they normally present an elevated energy density and high levels of sugars, fat, sodium and additives, they are hyper palatable, induce the child to frequent consumption and negatively influence future food preferences.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we observed an elevated prevalence of UPF consumption for all The total was lower for some variables due to missing information children. These results are similar to other studies that evaluated early childhood food consumption in Brazil [10,25]. UPF consumption in the first 2 years of life is not recommended because they normally present an elevated energy density and high levels of sugars, fat, sodium and additives, they are hyper palatable, induce the child to frequent consumption and negatively influence future food preferences.…”
Section: Discussionsupporting
confidence: 89%
“…For this reason, the broader recording schedule of the commercials was sought from 8:00 a.m. to 10:00 p.m. uninterrupted, differing from the design of other studies in which the recordings were intervals or only in the morning (Almeida et al, 2002;Vilaro, Barnett, Watson, Merten, & Mathews, 2017 Compared with parents who were not influenced by TV advertisements, parents who bought food influenced by TV advertisements had children (schoolchildren) who were more likely to consume cariogenic foods in front of the TV and who had higher rates of dental caries. The availability of food for family consumption depends directly on the choices made by parents at the time of purchase, and marketing is an important factor influencing these choices, especially when associating foods with low nutrient content with more favorable health conditions (Dallazen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…28 Another study conducted in 48 municipalities participating in the Brazil Without Misery Plan, in Southern Brazil, showed that 35.5% of children ate sugar before they were 4 months old, and that the prevalence of introducing sweet/salty crackers, petit swiss cheese and gelatin before they were six months old was 20.4%; 24.8% and 13.8%, respectively. 29 In the present study, most children under six months old did not eat sugar or processed and ultra-processed food.…”
Section: Discussionmentioning
confidence: 46%